Annealing atmosphere-dependent electrical characteristics and bias stability of N-doped InZnSnO thin film transistors. (July 2020) - Su, Jinbao; Yang, Hui; Ma, Yaobin; Li, Ran; Jia, Lanchao; Liu, Depeng; Zhang, Xiqing
Abstract: The dependence of electrical characteristics and gate bias stress stability of N-doped InZnSnO (IZTO:N) thin film transistors (TFTs) on annealing atmosphere was investigated. The annealing process was performed in air, O2 and N2, respectively, after the deposition of IZTO:N thin film by magnetron sputtering. All annealed IZTO:N films are amorphous and show a high transmittance in the visible light range. The N2 -annealed TFT has the highest saturation mobility ( μ SAT ) of 39.5 cm 2 V −1 s −1 and the lowest subthreshold swing ( SS ) of 0.40 V/decade. The air-annealed TFT shows similar mobility and SS to the N2 -annealed TFT while the O2 -annealed TFT shows the lowest mobility and the largest SS . We found that annealing atmosphere has impact on the bias stress stability of the TFTs. Bias stress induced threshold voltage shift of the O2 -annealed TFTs is reduced compared to that of air-annealed and N2 -annealed TFTs due to the decrease in oxygen vacancy.